Evaluasi Pelaksanaan Katekisasi Sakramen Penguatan di Rayon I Kota Semarang - Hartutik; Markus Dwi Setiawan (Jurnal Penelitian Pendidikan Agama Katolik, 2021)
The implementation of the Sacrament of Confirmation in the Semarang City Rayon has developed through direct coordination or via online media, studies of teaching material sources, the application of contextual methods and sharing of faith experience have not been maximized, only 58% of catechists have media, and only 75% of catechists believe in the mastery of the sacramental materials of the Chrismas; (2) The causes of suboptimal are there are differences in media tastes and learning methods, catechist educational background, lack of catechist training and regeneration, and not yet standardized teaching materials throughout the city of Semarang, (3) Optimization is carried out with periodic socialization and refreshment of materials, training pleasant teaching methods, open dialogue related to Semarang city rayon material standards, and catechist requirements with the spirituality of the preacher.